Tanggung Jawab Perusahaan Daerah Air Minum (Pdam) Terhadap Kerugian Konsumen Dan Melonjaknya Rekening Air Akibat Kebocoran Instalasi Dalam (Studi Pada Pdam Tirtanadi Provinsi Sumatera Utara) - Chandra Aditya Sapta; Ridho Mubarak; Windy Sri Wahyuni (Universitas Medan Area, 2022)
The management of clean water (drinking water) is managed by the Regional Drinking Water Company (PDAM). PDAM Tirtanadi often gets complaints from consumers regarding its services. Most of the consumer complaints to PDAM Tirtanadi are in the form of objections to paying bills that are not in accordance with the frequency of use so that it can cause consumers to suffer losses. Therefore, it is necessary to compensate for damages and rain-check effort to provide clean water. The research method used is a normative juridical approach. Research materials consist of primary, secondary and tertiary legal materials. This research is descriptive-analytical and to complete the research data it is supported by conducting interviews. The results of the study are the form of implementing compensation for negligence by the Regional Drinking Water Company (PDAM) in the form of restitution or refunds that will be included in the next month's account, the efforts of the Regional Drinking Water Company (PDAM) in providing clean water to consumers refers to clean water standards. drinking water based on the Minister of Health Regulation (PERMENKES) Number 907 of 2002 concerning Drinking Water Quality, namely passing standard tests including bacteriological, chemical, radioactive and physical requirements, PDAM's efforts to overcome soaring accounts due to leaks in internal installations by repairing pipes before the water meter (persil pipe) ), both repair costs and water usage are the responsibility of the PDAM, but if the pipe is damaged or leaks after the water meter, all costs are borne by the drinking water customer.